2010
DOI: 10.1016/j.freeradbiomed.2009.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of mercapturic acid conjugates of 4-hydroxy-2-nonenal and 4-oxo-2-nonenal metabolites in a smoking cessation study

Abstract: The breakdown of polyunsaturated fatty acids (PUFAs) under conditions of oxidative stress results in the formation of lipid peroxidation (LPO) products. These LPO products such as 4-hydroxy-2-nonenal (HNE) and 4-oxo-2-nonenal (ONE) can contribute to the development of cardiovascular and neurodegenerative diseases and cancer. Conjugation with glutathione, followed by further metabolism to mercapturic acid (MA) conjugates, can mitigate the effects of these LPO products in disease development by facilitating thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 42 publications
1
24
0
1
Order By: Relevance
“…The low protective effect at higher concentrations of ONE might be due to high reactivity of this aldehyde to cellular thiols and nucleophiles and/or the electrophilicity of the reduced product ONOL. 34,40) Reverse transcription-PCR analysis revealed that the mRNA for AKR1B14 is expressed in rat brain, lung, heart, stomach, liver, adrenal gland, kidney, ovary and testis, although the expression level was high in the adrenal gland and female rat liver (data not shown), as reported previously. 16,21) Considering its tissue distribution and broad substrate specificity (Table 1), AKR1B14 may be involved in detoxification of the reactive carbonyl compounds generated from lipid peroxidation and glycation, in addition to the regulation of adrenal catecholamine release through the PGF 2a synthase activity.…”
supporting
confidence: 82%
“…The low protective effect at higher concentrations of ONE might be due to high reactivity of this aldehyde to cellular thiols and nucleophiles and/or the electrophilicity of the reduced product ONOL. 34,40) Reverse transcription-PCR analysis revealed that the mRNA for AKR1B14 is expressed in rat brain, lung, heart, stomach, liver, adrenal gland, kidney, ovary and testis, although the expression level was high in the adrenal gland and female rat liver (data not shown), as reported previously. 16,21) Considering its tissue distribution and broad substrate specificity (Table 1), AKR1B14 may be involved in detoxification of the reactive carbonyl compounds generated from lipid peroxidation and glycation, in addition to the regulation of adrenal catecholamine release through the PGF 2a synthase activity.…”
supporting
confidence: 82%
“…Depletion of vitamin C levels in smokers was ameliorated within 3 months by supplementation with a vitamin cocktail containing vitamin C, alpha-tocopherol and folate [35]. Vitamin C supplementation was also effective at reducing levels of lipid peroxidation byproducts in smokers’ urine [36]. Using a metabolic approach, antioxidant supplementation in smokers was found to alter lipid profiles in plasma in a manner consistent with reductions in oxidative stress [37].…”
Section: Discussionmentioning
confidence: 99%
“…Decrease in plasma vitamin C was ameliorated by supplements of a vitamin cocktail containing vitamin C, α-tocopherol, and folate in smokers [29]. Vitamin C supplements were effective at reducing levels of lipid peroxidation in smokers [30]. Antioxidant supplements altered plasma lipid profiles in smokers in a manner consistent with the reduction in oxidative stress [31].…”
Section: Anthocyanin Supplements Increase Oxidative Stress In Young Hmentioning
confidence: 96%